Association among Maternal Obesity, Cervical Length, and Preterm Birth - Palatnik, Anna; Miller, Emily S.; Son, Moeun; Kominiarek, Michelle A. (American Journal of Perinatology, 2017)
Objective The objective of this study was to determine if mid-trimester cervical length is associated with the inverse relationship between maternal body mass index (BMI) at delivery and spontaneous preterm birth (SPTB).Materials and Methods This was a retrospective cohort of women with a singleton pregnancy without prior SPTB who underwent routine transvaginal cervical length assessment between 18 and 24 weeks. Women were categorized into four BMI groups: (1) 18.5 to 24.9, (2) 25 to 29.9, (3) 30 to 34.9, and (4) ≥ 35 kg/m2. Univariable and multivariable analyses were conducted to determine whether BMI group was associated with SPTB at < 37, 34, or 32 weeks independent of the cervical length.Results Of the 18,100 women in this analysis, 43.5% had a BMI ≥ 30. In univariable analysis, increasing BMI group was associated with longer cervical length but not with cervical length < 10th percentile. SPTB at < 37, 35, and 32 weeks was less common among women with higher BMI. In multivariable regression, a higher BMI group was associated with a lower frequency of SPTB at 37 weeks (adjusted odds ratios [aORs] of 0.64, 0.68, and 0.51), at 34 weeks (aORs of 0.53, 0.54, and 0.31) and at 32 weeks (aORs of 0.47, 0.60, and 0.27) for BMI groups 2 to 4, respectively. This association persisted even when cervical length was entered into the model as a covariate.Conclusion Women with a higher BMI group had longer mid-trimester cervical length, and correspondingly reduced SPTB. However, the decreased risk of SPTB was not associated with cervical length. The reason for the potential protective effect from prematurity is unknown and its mechanisms require further investigation.
Keywords: cervical length; body mass index; preterm birth; spontaneous preterm birth